Technical and tactical analysis of women`s volleyball - Inkinen, V.; Häyrinen, M.; Linnamo, V. (Biomedical Human Kinetics, 2013)
Introduction: The study aim was to construct a technical and tactical analysis of women`s volleyball based on notational analysis in top-level and junior women`s European volleyball matches, to compare these two levels, and to clarify the differences between the winners and losers of a set.